A cross-sectional observational study on allergen-specific IgE positivity in a southeast coastal versus a southwest inland region of China - Zeng, Guangqiao (Sci Rep, 2017)
Few studies addressed trans-regional differences in allergen sensitization between areas within a similar latitudinal range but with distinct geomorphological features. We investigated specific IgE (sIgE) positivity to common allergens in populations from two southern China provinces. Using a uniformed protocol, serum samples were collected from 2778 subjects with suspected atopy in coastal Guangdong and inland Yunnan. The overall prevalence of sIgE positivity were 57.8% (95% CI: 56.0%, 59.6%) from Guangdong vs 60.9% (95% CI: 59.1%, 62.7%) from Yunnan. House dust mite (d1) was the most common allergen in both regions. Among d1-sensitized subjects, only 35.7% (208/583) in Guangdong and 22.9% (147/642) in Yunnan tested positive for d1 alone. Among those poly-sensitized d1-positive subjects, cockroach was the most common co-sensitizing aeroallergen. 41.9% of the d1-sensitized Guangdong subjects showed high-class sIgE reactivity (≥class 4), in contrast to a very low percentage of such reactivity in Yunnan. However, 36.3% of d1-sensitized subjects in Yunnan were concomitantly positive for tree pollen mix. Surprisingly, Yunnan subjects showed high prevalence of sIgE positivity for crabs and shrimps, either by overall or by age-group analysis, compared with their Guangdong counterparts (both P < 0.05). These findings may add to data about local allergies in China and worldwide.